Hospitalizations due to congenital syphilis in neonates: Associated factors from the prenatal care process Internações por sífilis congênita em neonatos: Fatores associados a partir do processo da atenção pré-natal Hospitalizaciones por sífilis congénita en recién nacidos: Factores asociados desde el proceso de la atención prenatal - Pitilin E.B. (2020)
© 2020, Universidad de La Sabana. All rights reserved.Objective: To identify the factors associated with hospitalizations due to congenital syphilis in neonates, based on the characteristics of prenatal care. Materials and method: A quantitative case-control study, conducted by applying a questionnaire to 65 puerperal women with their babies hospitalized from July to November 2017. The data were analyzed using logistic regression, according to the plan proposed in the hierarchical approach. Results: 20% of the hospitalizations were due to syphilis (cases) and 80% to other causes (control). The vulnerability risk (p = 0.036), previous history of sexually transmitted infection (p = 0,006), use of oral contraceptives (p = 0.011) and parity (p = 0.043) variables were statistically significant. The absence of the partner during the consultation (p = 0.028), failure to perform a rapid test for syphilis (p = 0.035) and educational activity for the partner (p = 0.033) were also associated with the occurrence of the outcome, in addition to the variables of the newborn: low birth weight (p = 0.025), not being on exclusive breastfeeding (p = 0.036) and not having had skin-to-skin contact (p = 0.043). Conclusions: Congenital syphilis has several risk factors for its occurrence. It was possible to observe that the assistance inequalities existing in care during the prenatal consultations directly reflect on the occurrence of this condition.